Examining fractal image processing and analysis - Nayak, Soumya Ranjan; Mishra, Jibitesh (IGI Global, 2020)
Digital image processing is a field that is constantly improving. Gaining high-level understanding from digital images is a key requirement for computing. One aspect of study that is assisting with this advancement is fractal theory. This new science has gained momentum and popularity as it has become a key topic of research in the area of image analysis. Examining Fractal Image Processing and Analysis is an essential reference source that discusses fractal theory applications and analysis, including box-counting analysis, multi-fractal analysis, 3D fractal analysis, and chaos theory, as well
Keywords: Computer vision; Image processing / Digital techniques; Image analysis